Associations of blood biomarkers with glomerular filtration rate in patients with TIA and stroke: population-based study. Issue 1 (3rd September 2020) - Kelly, Dearbhla M.; Li, Linxin; Burgess, Annette I; Poole, Deborah L; Duerden, Julia M; Rothwell, Peter M.
Abstract : Background and purpose: Non-traditional risk factors such as chronic inflammation, oxidative stress and thrombogenic factors are believed to contribute to the excess stroke risk in chronic kidney disease (CKD) by triggering vascular injury and endothelial dysfunction. We aimed to determine how well a panel of biomarkers representative of these factors would correlate with estimated glomerular filtration rate (eGFR) in patients with recent transient ischaemic attack (TIA) or stroke. We also investigated whether eGFR would confound previously reported associations between biomarkers and mortality. Methods: We studied a panel of 16 blood biomarkers related to inflammation, thrombosis, atherogenesis and cardiac or neuronal cell damage in TIA or ischaemic stroke in a population-based study (Oxford Vascular Study). Biomarker levels were log-transformed and correlated with eGFR, adjusted for age. Cox proportional hazard models were used for survival analysis. Results: Among 1297 patients with TIA or stroke, 52.7% (n=684) of patients had CKD (eGFR <60 mL/min/1.73 m 2 ). There was a moderate correlation between log-eGFR and the log-transformed soluble tumour necrosis factor receptor-1 (R 2 =0.21), attenuating with adjustment for age (R 2 =0.12). There were moderate-to-strong correlations with markers of cardiac injury, N-terminal pro-brain natriuretic peptide and heart-type fatty acid binding protein (hFABP, R 2 =0.14 and 0.34, respectively). The strongest correlation after adjustment for age was between hFABP and eGFR (R 2 =0.20). Adjusting for eGFR did not impact any biomarker associations with mortality. Conclusions: Correlations between biomarkers related to inflammation and thrombosis with renal dysfunction in the setting of cerebrovascular events were generally modest after adjustment for age, suggesting that putative risk factors such as chronic inflammation or coagulopathy are unlikely to be important stroke mechanisms in patients with CKD.